Anticoccidial Effect of a Negilla sativa Seed-based Diet on Eimeria tenella Infection in Chickens - Kadhim , Latif Ibrahim (International Journal of Poultry Science, 2017)
Background and Objective: Eimeria tenella (E. tenella) infection is one of the most common and widely distributed parasitic diseases in chickens. Anticoccidial agents are used to treat the disease; however, due to the rise of drug-resistant strains and the ban of anticoccidials in many countries, alternative treatments are necessary. This study was conducted to analyze the effectiveness of Nigella sativa crushed seeds and ionophore salinomycin on E. tenella infection in broiler chickens. Methodology: One hundred one-day-old broiler chicks were divided into 4 equal groups. Group 1 (G1) was fed a basal anticoccidial-free diet containing 1% crushed Nigella sativa seeds and Group 2 (G2) was fed a basal diet containing 60 g t–1 of salinomycin for 35 days. Groups 3 (G3) and Group 4 (G4) were fed the basal diet only. G1, G2 and G3 were challenged with 1×104 sporulated oocysts of E. tenella and G4 served as the unchallenged control group. Results: The results revealed significant increases in glutathione (GSH) concentration, glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and catalase (CAT) activities at days 28 and 35 in G1 compared to G3 group. Nevertheless, a significant decrease in plasma malondialdehyde (MDA) was found in G1, G2 and G4 following the E. tenella challenge. Furthermore, G1 had significantly minor intestinal lesions scores and lower oocyte shedding compared to G3. Conclusion: It is concluded that Nigella sativa can be used to prevent and monitor avian Coccidiosis.